Cathepsin D as biomarker in cerebrospinal fluid of nusinersen‐treated patients with spinal muscular atrophy. (4th May 2022) - Schorling, David C.; Kölbel, Heike; Hentschel, Andreas; Pechmann, Astrid; Meyer, Nancy; Wirth, Brunhilde; Rombo, Roman; ,; Sickmann, Albert; Kirschner, Janbernd; Schara‐Schmidt, Ulrike; Lochmüller, Hanns; et al.
Abstract: Background and purpose: The therapeutic landscape of spinal muscular atrophy (SMA) has changed dramatically during the past 4 years, but treatment responses differ remarkably between individuals, and therapeutic decision‐making remains challenging, underlining the persistent need for validated biomarkers. Methods: We applied untargeted proteomic analyses to determine biomarkers in cerebrospinal fluid (CSF) samples of SMA patients under treatment with nusinersen. Identified candidate proteins were validated in CSF samples of SMA patients by Western blot and enzyme‐linked immunosorbent assay. Furthermore, levels of peripheral neurofilament heavy and light chain were determined. Results: Untargeted proteomic analysis of CSF samples of three SMA type 1 patients revealed the lysosomal protease cathepsin D as a candidate biomarker. Subsequent validation analysis in a larger cohort of 31 pediatric SMA patients (type 1, n  = 12; type 2, n  = 9; type 3, n  = 6; presymptomatically treated, n  = 4; age = 0–16 years) revealed a significant decline of cathepsin D levels in SMA patients aged ≥2 months at the start of treatment. Although evident in all older age categories, this decline was only significant in the group of patients who showed a positive motor response. Moreover, downregulation of cathepsin D was evident in muscle biopsies of SMA patients. Conclusions: We identified a decline of cathepsin D levels in CSF samples of SMA patients under nusinersen treatment that was more pronounced in the group of "treatment responders" than in "nonresponders." We believe that our results indicate a suitability of cathepsin D levels as a possible biomarker in SMA also in older patients, in combination with analysis of peripheral neurofilament light chain in adolescents or alone in adult patients. Abstract : Cathepsin D declines in cerebrospinal fluid of nusinersen‐treated spinal muscular atrophy (SMA) patients aged 2 months or older at start of therapy. The decline appears to be associated with response to treatment and indicates suitability as a prognostic biomarker in SMA.